Dampness defects on wall using infrared thermography at Pasar Besar Siti Khadijah, Kota Bharu Kelantan / Norida Maziantie Muhammad and Hasnan Hashim - Muhammad, Norida Maziantie; Hashim, Hasnan (2023)
Using infrared thermography for the analysis of buildings and structures is reliable and accurate. To measure the extent of dampness to a structure or building, an infrared scanner detects energy and maps the temperature contours over the surface of a target object. There is consideration of the application of infrared thermography in two specific situations - the delamination of external/ internal wall finishes and the assessment building’s physical condition. However, this study will focus on dampness on the building surface as well as the causes that affect this problem through the use of infrared thermography. Accordingly, a samples test (imager pictures) was taken to find the cause and effect of the occurrence of the defect dampness in the case study. From the research done, it can be concluded that there is indeed an effect of humidity on the walls of Pasar Besar Siti Khadijah, that is from an average temperature of 30 degrees Celsius, the colour from the observation of the thermograph image is purple which the indicator from the device shows in the lower range, the relative humidity is 70 percent to 79.4 percent. This percentage also shows the presence of moisture in the air around the building. In addition, there are also various defects that exist which show the action of this dampness. Finally, from the findings of this study, it is to identify the existence of this dampness. The data and findings obtained can be used by the Kota Bharu Municipal Council and vendors to ensure the safety of consumers and residents of the market as well as being able to carry out better maintenance plans in the future.